A novel wound dressing based on a Konjac glucomannan/silver nanoparticle composite sponge effectively kills bacteria and accelerates wound healing. (1st March 2018) - Chen, Honglei; Lan, Guangqian; Ran, Luoxiao; Xiao, Yang; Yu, Kun; Lu, Bitao; Dai, Fangying; Wu, Dayang; Lu, Fei
Highlights: Silver nanoparticles were prepared with green deoxidizer egg white. Silver nanoparticles loaded Konjac Glucomannan composite sponges were developed. The designed composite sponge possessed excellent antibacterial activity. The designed composite sponge displayed no significant cytotoxicity on L929 cells. Animal experiments have shown that wound healing can be effectively promoted. Abstract: A novel Konjac glucomannan/silver nanoparticle (KGM/AgNP) composite sponge was successfully prepared via a simple 2-step method for biomedical applications as wound-healing materials. First, AgNPs were prepared with green deoxidizer egg white. Then, KGM powder was added to the AgNP solution and stirred vigorously, and the composite sponge was obtained by freeze-drying. The KGM/AgNP composite sponge showed excellent water absorption and water retention, and considerable mechanical properties. KGM/AgNP composite sponges displayed good antibacterial activity against test microorganisms. In vitro cytocompatibility testing showed that L929 cells could survive well in the presence of KGM/AgNPs, indicating that KGM/AgNPs have good cytocompatibility. Animal models showed that the KGM/AgNP composite sponges effectively accelerated wound healing, and histological findings showed that they promoted fibroblast growth and accelerated epithelialization. The experimental results showed that KGM/AgNP composite sponges have great potential in promoting wound healing.